Risk of suicide in patients with thyroid cancer: protocol for a systematic review and meta-analysis - Chen Li; Mengmeng Zhang; Quan Wang; Yingjiang Ye; Kewei Jiang (BMJ Open)
Introduction In recent years, the incidence of thyroid cancer has increased manyfold and young adults, who have a greater financial burden and occupational stress, comprise a large number. Previous studies have shown mixed results, even distinct results, on suicide rates among thyroid cancer survivors. As the overdiagnosis and overtreatment of thyroid cancer has gradually become a topical issue, the study aims to summarise the risk of suicide among patients with thyroid cancer to provide robust evidence of the effects of thyroid cancer on suicide.Methods and analysis A total of six databases (MEDLINE, Embase, Web of Science Core Collection, PsycINFO, CINAHL and Google Scholar) will be searched according to MeSH, subheadings, and free words, and the planned search date is 31 Jnauary 2024. The search strategy had three parts, such as suicide, cancer and epidemiological studies, moreover, we will collect the detailed suicide information by reviewers’ extraction. Standard mortality ratio (SMR) was used as the outcome measure, when SMRs were not available, the risk ratio, HR and detailed number of suicides were extracted to calculate the SMRs.Ethics and dissemination The Institutional Review Board of Peking University People’s Hospital provided ethical approval exemption and approved the data collection and subsequent analyses in accordance with the Declaration of Helsinki as revised in 2013.PROSPERO registration number CRD42023445542.